An incurable case of love. 5 - Enjoji, Maki (Shojo beat manga., 2020)
"Nurse Nanase has striven to once again meet the prince of her dreams, so how is it he's become such an aggravating doctor?! After witnessing a handsome and charming young doctor save a stranger's life five years ago, Nanase Sakura trained to become a nurse. But when she meets the doctor again and they start working together, she finds Kairi Tendo to be nothing like the man she imagined him to be!... The Dark Lord Kairi finally falls for Nanase, the Valiant One! Regardless, they face another trial! Nanase became a nurse to chase after Dr. Kairi Tendo. Now the feelings are mutual, and they've become a couple. It seems their love should only deepen from here on out, but when Nanase tries to help a certain someone, it leads to a disruption in their romance!"--Provided by publisher.